The London joint stock banks, (their rise, progress, and present condition) (Longman[etc], 1855)
Being the repr. of a paper read before the "Statistical Section" of the "British Association for the advancement of Science" at St.George's Hall, Liverpool, in September, 1854, and publ. in the Bankers' Magazine of October and November, 1854.